Effect of three doses of biostimulant with two types of substrate on the asexual propagation of red pitahaya (hylocereus hybridum) cuttings, under greenhouse conditions, Independencia – Huaraz – Ancash (Aporte Santiaguino, 2024)
The research was conducted from December 2021 to July 2022. It aimed to evaluate the effect of three doses of biostimulant, with two types of substrate, on the asexual propagation of red pitahaya Hylocereus hybridum cuttings under greenhouse conditions. The completely randomized design was used, in a 3 x 2 factorial arrangement and 4 repetitions. The treatments were: T1 (without Bio Algae + 7 Sand: 3 Compost), T2 (35 ml of Bio Algae / 20L + 7 Sand: 3 Compost), T3 (65 ml of Bio Algae / 20L + 7 Sand: 3 Compost), T4 (Without Bio Algae + 7 Sand: 3 Humus), T5 (35 ml of Bio Algae / 20L + 7 Sand: 3 Humus), T6 (65 ml of Bio Algae / 20L + 7 Sand: 3 Humus). The variables evaluated were: Number of shoots, shoot length, number of roots, root length, root weights and root area. The results indicated that there are no statistically significant differences in the types of substrate and in the interaction between biostimulant dose and substrate types. However, statistically significant differences were found with respect to biostimulant doses. Dose D2 (65 ml of Bio Algas/20L) obtained the best results in number of shoots with 2.38 units, shoot length with 22.34 cm, number of roots with 4.05 units, root length with 12.45 cm, fresh weight with 9.93 g, dry weight with 4.69 g and root area with 92.01 cm2.
Keywords: Propagation; Biostimulant; Substrate; Pitahaya